PENGARUH PERMAINAN LOMPAT TALI TERHADAP PERKEMBANGAN MOTORIK KASAR ANAK USIA DINI - Andini, Yuli Tri; Syamsudin, M. Anas; Ulansari, Fita (JP2KG AUD (Jurnal Pendidikan, Pengasuhan, Kesehatan dan Gizi Anak Usia Dini), 2022)
Traditional games are the nation's cultural heritage that has various benefits in aspects of child development, physical motoric development is one of them. There are also many kinds of traditional games, one of which is the jump rope game. This study aims to determine the implementation of the jump rope game in developing gross motor skills. The method used is descriptive qualitative research subjects aged 4-5 years in Kindergarten Dharma Indria II Setail Banyuwangi, data collection techniques using observation, interviews, and documentation. The results showed that the traditional jumping rope game could develop children's gross motor skills.Traditional games are the nation's cultural heritage that have various benefits in aspects of child development, physical motoric development is one of them. There are also many kinds of traditional games, one of which is the jump rope game. This study aims to determine the implementation of the jump rope game in developing gross motor skills. The method used is descriptive qualitative research subjects aged 4-5 years in Kindergarten Dharma Indria II Setail Banyuwangi, data collection techniques using observation, interviews, and documentation. The results showed that the traditional jumping rope game could develop children's gross motor skills.